Drosophila heart cell movement to the midline occurs through both cell autonomous migration and dorsal closure - Haack, Timm; Schneider, Matthias; Schwendele, Bernd; Renault, Andrew D. (Elsevier, 2014)
The Drosophila heart is a linear organ formed by the movement of bilaterally specified progenitor cells to the midline and adherence of contralateral heart cells. This movement occurs through the attachment of heart cells to the overlying ectoderm which is undergoing dorsal closure. Therefore heart cells are thought to move to the midline passively. Through live imaging experiments and analysis of mutants that affect the speed of dorsal closure we show that heart cells in Drosophila are autonomously migratory and part of their movement to the midline is independent of the ectoderm. This means that heart formation in flies is more similar to that in vertebrates than previously thought. We also show that defects in dorsal closure can result in failure of the amnioserosa to properly degenerate, which can physically hinder joining of contralateral heart cells leading to a broken heart phenotype.